Rumus fungsi f(x) = ax + b . jika nilai f(1)= -2 dan nilai f(-2)= -11, maka nilai dari a+b adalah
F(1) = a(1) + b
-2 = a + b ……………….[1]
f(-2) = a(-2) + b
-11 = -2a + b ………….[2]
eliminasi pers [1] dan [2] :
a + b = -2
-2a + b = -11
____________–
3a = 9
a = 9/3
a = 3
substitusi nilai a ke salah satu persamaan :
-2 = a + b
-2 = (3) + b
(3) + b = -2
b = -2-3
b = -5
sehingga :
a+b = 3+(-5)
= -2 <—– Jawaban
F(1)=-2
f(1) = a1 + b = -2
f(-2) = -11
f(-2) = a-2 + b = -11
pakai spldv
-2a + b = -11 [1] = -2a + b = -11
a + b = -2 [-2] = -2a + (-2b) = 22
= -b = 11,, maka b = -11
substitusikann.
a + b = -2
a + (-11) = -2
a = -2 + 11
a = 9.
bukti..
f(x) = ax + b
f(1) = 9.1 + (-11)
f(1) = -2